2019
DOI: 10.4103/ijpvm.ijpvm_235_17
|View full text |Cite
|
Sign up to set email alerts
|

Application of social cognitive theory to prevent waterpipe use in male high-school students in Kerman, Iran

Abstract: Background:The growing supply and prevalence of waterpipe (WP) smoking among Iranian adolescents have become a concern for both families and policymakers. The aim of this study was to determine the factors underlying WP use and also to design an intervention program based on social cognitive theory (SCT) aimed to reduce the demand for WP smoking among male adolescents.Methods:This quasi-experimental study involved 189 high-school students in Kerman, Iran, who were split into two groups, an intervention group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…In line with this research, Mailey and McAuley (2014) had found that educational interventions based on the SCT could augment participants' self-regulation. However, the results of the present study did not support the reports in Rajabalipour et al (2019), probably due to the discrepancy in the study groups, as their investigation was based on utilizing the SCT in preventing the use of water pipes at high schools for boys.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with this research, Mailey and McAuley (2014) had found that educational interventions based on the SCT could augment participants' self-regulation. However, the results of the present study did not support the reports in Rajabalipour et al (2019), probably due to the discrepancy in the study groups, as their investigation was based on utilizing the SCT in preventing the use of water pipes at high schools for boys.…”
Section: Discussioncontrasting
confidence: 99%
“…Of the total articles included in this study, 13 studies were from Iran [20][21][22][23][24][25][26][27][28][29][30][31][32] , 1 article from the UK 33 , 1 from Syria 34 , 1 from Baghdad 35 , 1 from the Midwest 36 and 4 other studies from the United States [37][38][39][40] .…”
Section: Resultsmentioning
confidence: 99%
“…In terms of period, 5 studies were conducted in 2019-2020 20,25,32,38,39 , 4 studies in 2018 21,22,35,36 , 2 in 2017 23,28 , 5 in 2015-2016 26,27,29,30,36 , 4 studies in 2014 33,34,37,40 and 1 in 2011 24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations